2020
DOI: 10.1016/j.topol.2020.107235
|View full text |Cite
|
Sign up to set email alerts
|

Generating functions and topological complexity

Abstract: We examine the rationality conjecture raised in [1] which states that (a) the formal power series r≥1 TCr+1(X) · x r represents a rational function of x with a single pole of order 2 at x = 1 and (b) the leading coefficient of the pole equals cat(X). Here X is a finite CWcomplex and for r ≥ 2 the symbol TCr(X) denotes its r-th sequential topological complexity. We analyse an example (violating the Ganea conjecture) and conclude that part (b) of the rationality conjecture is false in general. Besides, we establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Indeed, a remarkable 3-cell complex X is constructed in [31] with the property that cat(X ×X) = cat(X) = 2. In [14], the higher topological complexities of X were shown to be TC r (X) = r = cat(X r ) (r ≥ 2). In view of Theorem 1.1, this yields P X (1) = 1 < cat(X).…”
Section: Tc-generating Function and Ls-logarithmicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a remarkable 3-cell complex X is constructed in [31] with the property that cat(X ×X) = cat(X) = 2. In [14], the higher topological complexities of X were shown to be TC r (X) = r = cat(X r ) (r ≥ 2). In view of Theorem 1.1, this yields P X (1) = 1 < cat(X).…”
Section: Tc-generating Function and Ls-logarithmicitymentioning
confidence: 99%
“…It should be noted that, in this example, P X (1) = cup(X), the cup-length of X, a situation that, to the best of our knowledge, holds in all cases where all TC r (X) are known. It is tempting to insert this clause in the modified form of the rationality conjecture at the end of [14].…”
Section: Tc-generating Function and Ls-logarithmicitymentioning
confidence: 99%
“…As is observed in [3], Question 1.1 is asking whether or not TC r+1 (X) = TC r (X) + cat(X) for all r large enough. Farber, Kishimoto and Stanley [3] proved that if TC r (X) = zcl r (X; k) and cat(X) = cup(X; k) for some field k and all r large enough, then F X (x) satisfies the condition in Question 1.1, where zcl r (X; k) and cup(X; k) denote the r-th zero-divisors cup-length and the cup-length of X over k, respectively. They also showed that F X (x) does not always satisfy the condition in Question 1.1.…”
Section: Introductionmentioning
confidence: 98%
“…By applying Theorem 1.4, we give a rational space X, to which the criterion of Farber, Kishimoto and Stanley [3] mentioned in Section 1 does not apply, but F X (x) satisfies the condition of Question 1.1.…”
Section: Introductionmentioning
confidence: 99%
“…Here cat denotes the Lusternik-Schnirelmann category. While a counter-example to the rationality conjecture for finite CW-complexes was found in [FKS20], the rationality conjecture for groups of type F remains open. It is known to hold, e.g.…”
Section: Introductionmentioning
confidence: 99%